Modified eaudiobook Book one in the manipulated series. - North, Harper (Manipulated, 2018)
What if the sky was deadly? Fin has never stepped foot on the surface of the Earth. Working the mines, deep below, has been the only life she's ever known. The underground is nothing more than an existence of sweat and monotony in service to the Enhanced Human Coalition—the genetically-modified who control the underground from the world above. Every Dweller underground understands that you serve the EHC up top, or you don't eat. Two hundred years after the planet's magnetic poles began to flip, Earth's surface has become irradiated and unsustainable. As the land, water, and even the air grew toxic, the underprivileged were doomed to a life of hard labor underground, while the Enhanced Human Coalition on the surface enjoy their spoils. But now, Fin and her friends discover a stolen piece of EHC tech that modifies genetics, giving them the abilities of those up top—varied levels of increased strength, intelligence, and adaptation to the surface's harsh conditions. The theft of this technology triggers a manhunt, forcing them to flee to the most dangerous place they could possibly go . . . aboveground. Can she save a world broken in two?